Identification Of Subsurface Lithological Units Using Electrical Resistivity Modelling In A Landslide-Prone Area Of Dlingo, Bantul, Yogyakarta - Rahmawati Fitrianingtyas; Chairul Amri; Khafidh Nur Aziz; Hilma Lutfiana; Rial Dwi Martasari; Uli Ulfa (Jurnal Fisika Unand, 2026)
The Dlingo area in Bantul Regency, Yogyakarta, is characterized by steep slopes and volcanic deposits that contribute to high landslide susceptibility, as evidenced by destructive events in 2021. This study aims to characterize subsurface conditions controlling slope instability using electrical resistivity modeling. Geoelectric data were acquired using the Wenner configuration along four survey lines, consisting of three slope-parallel profiles and one slope-perpendicular profile, each 225 m long with 15 m electrode spacing. Apparent resistivity data were processed and inverted using Res2Dinv to generate two-dimensional (2D) resistivity sections. The results consistently reveal three principal resistivity zones across all profiles: (1) a high-resistivity unit (approximately 33,9–642 Ωm) interpreted as relatively compact to slightly weathered tuff, (2) a moderate-resistivity layer (1.79–33.9 Ωm) corresponding to weathered volcanic deposits, and (3) a low-resistivity zone (<1.79 Ωm) interpreted as water-saturated or highly conductive material developed along the lower slope. The recurrent resistivity contrast between the weathered layer and the underlying conductive zone suggests a hydrogeological boundary that may facilitate pore-water accumulation and contribute to slope instability. These findings provide a geophysically constrained conceptual model of subsurface controls on slope instability in volcanic terrains.